Social cost-benefit analysis of investment in rehabilitation of multipurpose small reservoirs in northern Ghana using an ecosystem services-based approach - Bekoe, J.; Balana, Bedru; Nimoh, F. (Elsevier, 2021)
Multipurpose small reservoirs are essential infrastructure in providing water for irrigation and non-irrigation uses in water stress areas of northern Ghana. Unfortunately, the flow of multiple ecosystem services from small reservoirs have been declining over several years due to lack of rehabilitation and poor management. Using selected multipurpose small reservoirs and available secondary and survey data, this paper applied an ecosystem services-based approach in the economic analysis of investment in rehabilitation of small reservoirs in northern Ghana. The findings reveal that private financial returns from irrigated crops have negative net present value (NPV) and an internal rate of return (IRR) lower than the cost of capital, implying a lack of economic incentive for private investors in their rehabilitation. However, accounting for the multiple ecosystem services such as livestock watering, fisheries, recreation services, domestic water, and climate regulation show positive NPV and high return on capital (IRR up to 43%). Policy choices would be biased against reservoir development if stakeholders consider only irrigation benefits. Based on the findings we recommend public investment in rehabilitation of multi-purpose small reservoirs to harness the multiple ecosystem services and community livelihoods. We further recommend public–private-user partnership business model to address current management inefficiency and optimize the flows of ecosystem services from small reservoirs to wider community.